Effects of Exogenous Selenium Species and Arbuscular Mycorrhizal Fungi on Selenium Uptake in Soybean - Haode Zhu; Wenjing Xing; Qimin Chen; Yuanzhe Ma; Jing Yang; Shangyan Hao; Fuyong Wu (Agronomy, 2025)
Selenium (Se) is an important micronutrient for the maintenance of human health. In China, however, the population is more severely deficient in Se. Soybean is an important grain and oil crop in the world and serves as a major dietary source. The development of Se biofortification of soybeans may be an effective measure to address human Se deficiency. Arbuscular mycorrhizal fungi (AMF) are ubiquitous soil microorganisms that can enhance nutrient uptake in host plants. So, it is necessary to investigate whether soybean inoculated with AMF can biofortificate Se. In this experiment, we studied the impact of the exogenous application of three Se species (selenite, selenate, and selenomethionine) and two AMF species (Funneliformis mosseae and Glomus versiforme) on Se uptake in soybean seedlings. The results showed that the inoculation of AMF significantly (p < 0.05) improved biomass and P concentration in soybeans. Regardless of exogenous Se addition, the inoculation of AMF improved the Se transfer factor and significantly (p < 0.05) increased Se translocation to the soybean shoot. The inoculation of AMF also significantly (p < 0.05) increased the percentage of available Se in soil with selenite addition. Based on these findings, the combined application of exogenous Se and AMF inoculation represents a viable strategy for the Se biofortification of soybeans.